Do we have the right kind of diversity in Innovation Policies among EU Member States? - Reinhilde Veugelers (WWWforEurope, 2015)
This contribution focuses on the heterogeneity in innovation capacity within Europe across its different Member State. Who are the leading and who are the lagging EU countries? Is there a trend towards convergence over time? And how has the crisis affected this trend of convergence? We then take a look at the research and innovation policies which the EU countries have in place and try to assess whether these policies match with the heterogeneous EU countries' innovation capacity positions. We examine both the budgets allocated by EU Member States to R&I as well as the various kinds of R&I policy programmes being deployed. More particularly, we examine how heterogeneous the deployment of policy instruments is across EU member states and whether this matches with the heterogeneity in innovation capacity development among EU countries. Notwithstanding the large and increasing heterogeneity among EU countries in innovation capacity development, the evidence on innovation policies in EU countries shows a relative homogeneity of policy mixes in different countries. Current innovation policy mixes of instruments do not well reflect the countries' levels of innovation capacity development.
Keywords: O31; O38; 330; Innovation; Innovation policy; Institutional reforms; Multi-level governance